1993
DOI: 10.1116/1.578666
|View full text |Cite
|
Sign up to set email alerts
|

Copper deposition by electron cyclotron resonance plasma

Abstract: An electron cyclotron resonance plasma reactor has been built in order to study the filling of high aspect-ratio features on semiconductor devices with metal. The reactor produces a plasma of copper which is nearly 100% ionized at the substrate, without the use of any buffer or carrier gas. The ion flux is dependent on both the feed rate of copper neutrals into the plasma region, and on the microwave power absorbed in the plasma. Solid filling of features having aspect ratios as high as 4.2 is demonstrated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Generally speaking, a higher deposition rate can shorten the required deposition time which will prevent Cu atoms from sufficiently exposing to O 2 . This should be the main reason why the DC mode with larger sputtering power density tends to achieve pure Cu film while RF mode or smaller sputtering power density tends to form Cu film with Cu 2 We further studied the electrical resistivities and band gaps of the obtained Cu-based films. Among these, it is found that the pure Cu film and the Cu/Cu 2 O composite film both display an intriguing combination of metal and semiconductor characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally speaking, a higher deposition rate can shorten the required deposition time which will prevent Cu atoms from sufficiently exposing to O 2 . This should be the main reason why the DC mode with larger sputtering power density tends to achieve pure Cu film while RF mode or smaller sputtering power density tends to form Cu film with Cu 2 We further studied the electrical resistivities and band gaps of the obtained Cu-based films. Among these, it is found that the pure Cu film and the Cu/Cu 2 O composite film both display an intriguing combination of metal and semiconductor characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, it is found that the pure Cu film and the Cu/Cu 2 O composite film both display an intriguing combination of metal and semiconductor characteristics. For example, the electrical resistivities of a 31 nm-thick pure Cu film and a 72 nm-thick Cu/Cu 2 O (~10 at.% Cu 2 O) composite film are 1.2×10 −4 and 6.2×10 −5 Ω cm respectively; while the band gaps E g , which were estimated according to the prolongation (dotted lines) of linear sections of (Ahv) 2 -hv curves (solid lines) in Fig. 1, are 1.54 and 2.48 eV respectively for the 31 nm-thick pure Cu film and 72 nm-thick Cu/Cu 2 O composite film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 An ionized deposition flux can also be employed to influence the angular distribution of the deposited material, since the trajectories of charged species can be manipulated by the use of electric and/or magnetic fields. [15][16][17][18] A technique that can be used to generate highly ionized deposition fluxes is high power impulse magnetron sputtering (HiPIMS). [19][20][21][22][23] Previously, HiPIMS has been employed for the deposition of Ta films on substrates placed at an angle of 90 with respect to the sputtering target normal, yielding films with columns positioned along the substrate surface normal.…”
mentioning
confidence: 99%
“…This strategy has been extensively employed over the last decades to control film growth when deposition is preformed normal to the substrate surface [4][5][6][7]. Research has also demonstrated the ability of using ionized vapor fluxes to control film microstructure and morphology when deposition is carried out at grazing incidence (off-normal growth) [8][9][10]. However, the fundamental physical processes that determine the growth evolution when performing off-normal deposition using ionized fluxes are not fully understood.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%